Ensino contextualizado de biologia no ensino médio : desafios e possibilidades - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The objective of this research was to analyze how the pedagogic practice of the high school teacher of the public education network of the state of Goiás focuses on the use of contextualization in educational practice as well as contribute to the mitigation of the challenges so that the exercise of contextualized teaching is more effective In teaching Biology. The contextualized teaching was discussed by Vygotsky and Paulo Freire, and the official documents such as the National Curriculum Parameters (NCP) refer to contextualization as one of the guiding principles of teaching. In this sense, when examining how the implementation of the contextualized teaching in the discipline of Biology in Secondary Schools (SS) has occurred to the Secretary of State for Education, Culture and Sport (SEDUCE), we have tried to understand how teachers understand what is requested In the guiding documents and how this pedagogical practice occurs. For that, analyzes were carried out in official documents, books and periodicals, the conceptions of this teaching, besides those adopted by the Biology teachers of this teaching network. It was also intended to identify the forms of the practice of this teaching and the limitations encountered by these teachers in this exercise. In view of the results, an instructional material was developed to assist the teacher in the implementation of the contextualized teaching of Biology in the public education network of the state of Goiás. The work was based on: a) documental and bibliographic research, Approaches, conceptions and practices on the contextualized teaching of Biology reported in the scientific literature; B) in the field research, which, through a questionnaire applied to Biology professors of the state public school of Goiás, sought to collect information on the professional data, the forms of work, the conceptions about the researched subject and the difficulties faced in the Contextualised teaching exercise; C) in the professional experiences of the master's degree. The development of the project of this dissertation resulted in two distinct educational products: 1. Continuing education meetings of the teachers of the four Regional Assistant Secretaries of Education (SRE); 2. Introduction of Biology: contextualized activities, the suggested activities were adapted from the pedagogical possibilities presented and discussed with the teachers of the public education network of the state of Goiás during the meetings of continuing education. The analyzed data allowed to verify that there are several conceptions of contextualized teaching, but the teachers of Biology that work in High School in SEDUCE do not present such diversity of conceptions. Even in the face of the numerous challenges listed by these teachers, the contextualized teaching of biology has happened, although in an incipient way, far from what is recommended in the scientific literature
Contextualized teaching of biology in high school: Challenges and possibilities
Keywords: Educação contextual; Ensino de Biologia; Contextualização; Formação de professores; Contextual education; Teaching of Biology; Contextualization; Teachers training; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::EDUCACAO